Pengaruh Ukuran Perusahaan, Profitabilitas, Koneksi Politik dan Pengungkapan Corporate Social Responsibility Pada Tax Avoidance - Darmayanti, Pande Putu Biantari; Lely Aryani Merkusiawati, Ni Ketut (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p12, 2019)
The variables examined in this study are company size, profitability, political connections and disclosure of corporate social responsibility (CSR). The purpose of this study is to obtain empirical results regarding the effect of company size, profitability, political connections and disclosure of corporate social responsibility (CSR) on tax avoidance. This research was conducted on the Indonesia Stock Exchange (IDX). The number of samples taken as many as 38 manufacturing companies with nonprobability sampling method, especially purposive sampling. The research period is 2014-2017. Data collection is done by non-participant observation techniques. The data analysis technique used is multiple linear regression. The results of this study indicate that company size, political connections and disclosure of corporate social responsibility have no effect on tax avoidance while profitability has a negative effect on tax avoidance. The amount of profit obtained by the company is very influential on the company's actions to practice tax avoidance. Keywords: Tax avoidance, company size, profitability, political connections, disclosure of corporate social responsibility